Social Media Moderation Model on Entrepreneurial Intention among Students in Indonesia and Thailand - Fitri Fitri; Mutiarini Mutiarini; Giri Dwinanda; Chalog Tubsre; Pratanna Srisuk (AIBPM Publisher, 2026)
The rapid development of digital technology has transformed how students access information and develop entrepreneurial opportunities, with social media emerging as a key platform influencing entrepreneurial motivation. However, limited studies have examined its role as a moderating factor in strengthening entrepreneurial intention among university students. This study aims to analyze the influence of entrepreneurial mindset and educational support on entrepreneurial intention, with social media as a moderating variable. A quantitative approach was employed using survey data from 251 university students in Indonesia and Thailand (response rate: 78.4%), analyzed using moderation regression and t-tests in IBM SPSS Statistics. The results indicate that entrepreneurial mindset (? = 0.163; p = 0.008) and perceived education (? = 0.179; p 0.001) have significant positive effects on entrepreneurial intention, while social media shows the strongest influence (? = 0.400). The model demonstrates strong explanatory power (R² = 0.780; adjusted R² = 0.703) and is statistically significant (F = 197.912; p 0.001). Furthermore, social media significantly moderates both relationships, highlighting its strategic role in enhancing entrepreneurial intention and supporting the integration of social media-based learning in entrepreneurship education.